Salmon peptides limit obesity‐associated metabolic disorders by modulating a gut‐liver axis in vitamin D‐deficient mice. Issue 10 (27th August 2021) - Valle, Marion; Mitchell, Patricia L.; Pilon, Geneviève; Varin, Thibault; Hénault, Loïc; Rolin, Jonathan; McLeod, Roger; Gill, Tom; Richard, Denis; Vohl, Marie‐Claude; Jacques, Hélène; Gagnon, Claudia; et al.
Abstract: Objective: This study investigated the effects of a low‐dose salmon peptide fraction (SPF) and vitamin D3 (VitD3 ) in obese and VitD3 ‐deficient mice at risk of metabolic syndrome (MetS). Methods: Obese and VitD3 ‐deficient low‐density lipoprotein receptor (LDLr) −/− /apolipoprotein B100 (ApoB) 100/100 mice were treated with high‐fat high‐sucrose diets, with 25% of dietary proteins replaced by SPF or a nonfish protein mix (MP). The SPF and MP groups received a VitD3 ‐deficient diet or a supplementation of 15, 000 IU of VitD3 per kilogram of diet. Glucose homeostasis, atherosclerosis, nonalcoholic fatty liver disease, and gut health were assessed. Results: VitD3 supplementation increased plasma 25‐hydroxyvitamin D to optimal status whereas the VitD3 ‐deficient diet maintained moderate deficiency. SPF‐treated groups spent more energy and accumulated less visceral fat in association with an improved adipokine profile. SPF lowered homeostatic model assessment of insulin resistance compared with MP, suggesting that SPF can improve insulin sensitivity. SPF alone blunted hepatic and colonic inflammation, whereas VitD3 supplementation attenuated ileal inflammation. These effects were associated with changes in gut microbiota such as increased Mogibacterium and Muribaculaceae. Conclusions: SPF treatment improves MetS by modulating hepatic and gut inflammation along with gut microbiota, suggesting that SPF operates through a gut‐liver axis. VitD3 supplementation has limited influence on MetS in this model.